Comparative Grain-Size Measurements for Validating Sampling and Pretreatment Techniques in Terms of Solifluction Landforms, Southern Carpathians, Romania - Serban, Raul David; Sipos, György; Popescu, Mihaela; Urdea, Petru; Onaca, Alexandru; Ladányi, Zsuzsanna (Journal of Environmental Geography, 2015)
Grain-size distribution has become in the last years an important indicator in the analysis of periglacial processes and landforms. However, as they exhibit a complex sedimentology, careful sampling is required to draw meaningful conclusions. The aim of the present study was therefore to validate the sampling procedure carried out on solifluction forms and to evaluate the effect of sampling pretreatment during grain size analysis. A comparison between multiple measurements of grain size distribution using the laser diffraction method (LDM) was performed on 54 sediment samples collected from different solifluction landforms at different depths in the alpine area of the Southern Carpathians. The results of parallel measurements were compared using textural and statistical indicators. The received distributions reinforced the properness of field sampling procedure in most of the cases. The results of textural classification and fractional composition showed a high consistency between the two parallel measurements made on untreated and pretreated samples. An overall fining as a matter of etching was identified. Relative deviation increased and correlation decreased as pretreatment advanced. HCl etching resulted a greater deviation and variability in case of the sand fraction, H2O2 rather affected the silt fraction. The greatest deviations were experienced in case of landforms developed on crystalline limestone. Pretreatment of samples introduced a major uncertainty to further comparison and interpretation. Thus, multiple LD measurements on a representative group of samples from the entire sample set were suggested before the geomorphological or environmental interpretation of results to decrease the uncertainties and to validate the processes.